2010
DOI: 10.1007/s11018-010-9545-3
|View full text |Cite
|
Sign up to set email alerts
|

Erratum to: “Development of a Super-Stable Datum Point for Monitoring the Energy Scale of Electron Spectrometers in the Energy Range up to 20 keV” by D. Vénos, M. Zbořil, J. Kašpar, O. Dragoun, J. Bonn, A. Kovalík, O. Lebeda, N. A. Lebedev, M. Ryšavý, K. Schlösser, A. Špalek, and Ch. Weinheimer, Vol. 53, No. 3, pp. 305–312, July, 2010

Abstract: The long-term energy stability of the 7.5 keV and 17.8

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…Moreover, portions of about 7% and 10% of the incident 83 Sr and 85 Sr ions, respectively, were found in the surface contamination layers which exhibit different physicochemical properties than the corresponding bulk foil material. The above number was experimentally proved in the case of the implantation of 83 Rb into the similar Pt foil [25,26].…”
Section: Methodsmentioning
confidence: 80%
See 1 more Smart Citation
“…Moreover, portions of about 7% and 10% of the incident 83 Sr and 85 Sr ions, respectively, were found in the surface contamination layers which exhibit different physicochemical properties than the corresponding bulk foil material. The above number was experimentally proved in the case of the implantation of 83 Rb into the similar Pt foil [25,26].…”
Section: Methodsmentioning
confidence: 80%
“…In order to achieve this upper mass limit, a long-term stability of the energy scale of the main KATRIN electrostatic retardation β-ray spectrometer at the level of ±3 ppm (i. e., ±60 meV at 18.6 keV) for at least 2 months of continuous measurements is required. In this regard, suitability of the K-32 conversion electrons (kinetic energy of 17.8 keV) of 83m Kr (generated in the EC decay of 83 Rb) for monitoring of the KATRIN spectrometer energy scale stability was extensively studied in [25,26]. The results obtained unambiguously indicated that the electron sources prepared by 83 Rb ion implantation into metallic matrices should be preferred.…”
Section: Introductionmentioning
confidence: 99%
“…The systematic measurements of the energy stability of the 83m Kr conversion lines, carried out at the Mainz MAC-E filter spectrometer, were started with 83 Rb/ 83m Kr sources prepared by vacuum evaporation of 83 Rb onto carbon substrate. In the course of these measurements, which are reported elsewhere [28,29,30], it was realised that the sources fulfil the requirements for the time stability of the conversion line energy but exhibit only moderate retention of 83m Kr of about 15 %. The retention of 83m Kr represents the portion of 83m Kr atoms retained in the solid matrix of the source and thus useful for the calibration purposes.…”
Section: Implanted 83 Rb/ 83m Kr Sourcementioning
confidence: 93%
“…For this reason rubidium is vacuum evaporated onto a backing of Highly Oriented Pyrolytic Graphite (HOPG) or rigid graphite by the Nuclear Physics Institute Řež/Prague. Thereby roughly a mono-layer 83 Rb is placed onto the graphite [8]. Energy losses of electrons traveling through this layer are negligible.…”
Section: Rb\ 83m Kr Sourcesmentioning
confidence: 99%